Administração pública, direito e urbanismo: as Assembleias Municipais no sistema português de governo local - Condesso, Fernando Dos Reis (M+A. Revista Electrónica de Medioambiente, 2009)
General characterization of the autarchic powers with specification of the function of the Assembly Municipal and in the perspective inter-administrative, having present to his lawful centrality in the system of local government, it reinforced with a future occasionally solution of parliamentary of the executive legitimacy of the Chamber´s assembly, with exception of the president, the only that can have direct electoral legitimacy. To develop some International aspects, general pronunciation about the local management, conventions of border cooperation, Portuguese-Spanish, as European like bilateral, inspection and access to the information and promotion of the executive transparency.
Keywords: Public administration; Municipal assembly; Urban planning